Lincoln - Spielberg, Steven; Kushner, Tony; Day-Lewis, Daniel; Field, Sally; Strathairn, David; Gordon-Levitt, Joseph; Spader, James; Holbrook, Hal; Jones, Tommy Lee; Dreamworks Pictures; Twentieth Century-Fox Film (California : Twentieth Century Fox, 2012)
During his final turbulent months in office, Lincoln strives to convince war-ravaged America's bitterly divided government to abolish slavery. With fierce, unstoppable courage, Lincoln inspires a decision that will change history forever.
Based in part on the book'Team of rivals: the political genius of Abraham Lincoln' by Doris Kearns Goodwin
Special features: The journey to Lincoln ; Crafting the past ; Credits.
Director of photography, Janusz Kaminski ; executive producer, Daniel Lupi, Jeff Skoll, Jonathan King ; edited by, Michael Khan ; music by, John Williamns.
Daniel Day-Lewis, Sally Field, David Strathairn, Joseph Gordon-Levitt, James Spader, Hal Holbrook, Tommy Lee Jones.
LPF: P13.
DVD format, NTSC, Dolby Digital.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Drama; Lincoln, Abraham, -- 1809-1865 -- Military leadership -- Drama; United States -- History -- Civil War, 1861-1865 -- Drama